STRATEGI PEMBERDAYAAN GURU DALAM MENINGKATKAN MUTU PENDIDIKAN - W Widodo; Heru Sriyono (Faktor Jurnal Ilmiah Kependidikan, 2020)
Abstract: Quality of education is an important requirement in preparing superior human resources. But in reality the implementation of education has not been able to produce qualified graduates. These conditions, among others, caused by the empowerment of teachers. This research was conducted to analyze teacher empowerment strategy in improving education quality. The research used qualitative approach with descriptive method. Data obtained through literature review and analyzed descriptively-qualitative. The results showed that the improvement of the quality of education requires appropriate teacher empowerment strategies. Key words: education quality, empowerment, teacher.